An oh(1720 MHZ) maser and a nonthermal radio source insgr b2(m): An snr-molecular cloud interaction site? - Yusef-Zadeh, F.; Cotton, W.; Wardle, M.; Intema, Hubertus (Institute of Physics Publishing, 2016)
Sgr B2 is a well-known star-forming molecular cloud complex in the Galactic center region showing evidence of high energy activity as traced by the Kα neutral Fe I line at 6.4 keV, as well as GeV and TeV γ-ray emission. Here, we present Very Large Array and GMRT observations with respective resolutions of approx. 3.”5 x 1.”2 and 25” x 25” and report the detection of an OH(1720 MHz) maser, with no accompanying OH 1665, 1667, and 1612 MHz maser emission. The maser coincides with a 150 MHz nonthermal radio source in Sgr B2(M). This rare class of OH(1720 MHz) masers or the so-called supernova remnant (SNR) masers, with no main line transitions, trace shocked gas and signal the interaction of an expanding SNR with a molecular cloud. We interpret the 150 MHz radio source as either the site of a SNR–molecular gas interaction or a wind–wind collision in a massive binary system. The interaction of the molecular cloud and the nonthermal source enhances the cosmic-ray ionization rate, allows the diffusion of cosmic rays into the cloud, and produces the variable 6.4 keV line, GeV, and TeV γ-ray emission from Sgr B2(M). The cosmic-ray electron interaction with the gas in the Galactic center can not only explain the measured high values of cosmic-ray ionization and heating rates but also contribute to nonthermal bremsstrahlung continuum emission, all of which are consistent with observations.